Plagiarisme Mahasiswa Akuntansi: Dimensi Fraud Pentagon - Yolanda Sari Hendra; Deviani Deviani (Jurnal Eksplorasi Akuntansi, 2022)
This study aims to examine the elements of the fraud pentagon, namely pressure, rationalization, opportunity, competence, and arrogance against plagiarism of accounting students. This type of research is quantitative research. The population in this study were students of the S1 Accounting Study Program, Faculty of Economics, Universitas Negeri Padang with a total sample of 47 people. The sampling technique used is purposive sampling. Sources of data in this study are primary data and secondary data. Primary data obtained from answers to questionnaires that have been distributed to respondents. Secondary data was obtained from the Department of Accounting, Faculty of Economics, Universitas Negeri Padang, this data was the result of a research proposal turnitin. This research model uses multiple linear regression analysis. The result of this study indicate that pressure, rationalization, opportunity, and arrogance do not affect plagiarism of accounting students. However, the competence influence plagiarism of accounting students.